Cyber-activism and Waves of Communication Agitation: Ethnographic Considerations - Nicolas Aguilar-Forero (Íconos)
In this article I present the results of a multi-sited, collaborative and experimental ethnographic study that took place between 2012 and 2014. It was focused the communication practices of the organization Sons and Daughters for Identity and Justice and Against Forgetting and Silence (H.I.J.O.S. in Spanish). In particular, the analysis in this article focuses on the characteristics of the cyber activism of the Bogota based chapter of H.I.J.O.S. as an example of the politicized appropriation of distinctive online platforms by this group to share content, coordinate activities and for the resolution and transformation of internal conflicts. The analysis, developed in dialogue with key concepts from the anthropology of virtual worlds, attempts to promote reflection on the necessary displacements and the challenges of ethnographic fieldwork, in the context of the study of cyber activism in the contemporary world.